GLOBAL ANALYSES OF BRACHIOPOD FAUNAS THROUGH THE ORDOVICIAN AND SILURIAN TRANSITION: REDUCING THE ROLE OF THE LAZARUS EFFECT - Rong J.-Y.; Zhan R.-B.; Boucot A.J.; Harper D.A.T.; Neuman R.B. (My University, 2006)
Global analyses of 88 families and 284 genera of brachiopods from middle Ashgill, Late Ordovician, to early-middle Rhuddanian, Early Silurian, indicate that 18.6% and 12.5% of families and 51.0% and 41.3% of genera were eliminated in the first and second phases of the end-Ordovician mass extinction, respectively, with the total loss of 28.4% of families and 69.0% of genera in the crisis. New investigation demonstrates that brachiopods, at both generic and familial levels, suffered greater during the first phase than during the second phase. Four groups (victims, relicts, survivors, and new arrivals) are distinguished by their stratigraphical ranges. Generic survivors, occurring in the Kosov Province during the Hirnantian, can be split into three types with respect to their changing abundance: increasing, declining, and Lazarus taxa. Among the 88 genera that survived, numerous declining genera occurred in the Hirnantian: 16 Lazarus families and 18 Lazarus genera are provisionally known and may be regarded as end members of the declining type. Comparison of the abundance, population size, and distribution patterns of declining and Lazarus taxa shows important similarities between these two types which contribute to a better understanding of the nature of Lazarus taxa. In addition to these biological attributes, taphonomic failure and generally poor preservation, together with collecting bias and inadequate systematic data, are clearly involved. More collections will undoubtedly globally reduce the number of Lazarus taxa. A single, common refugium for end-Ordovician brachiopods probably did not exist; rather, these taxa used paleogeographically scattered locations in a range of environments for survival. © 2006 NRC Canada.
Keywords: Rhuddanian; Hirnantian; Paleozoic::Silurian::Llandovery::Rhuddanian; Палеозой::Силурийская::Лландоверийский::Рудданский; Paleozoic::Ordovician::Upper::Hirnantian; Палеозой::Ордовикская::Верхний::Хирнантский